(3JMaI GdQGFV aj CMcGe GdaQGFVs - (3GdGRgQj , eMeO Hf eMeO Hf eMehO GdGRgQj GdMfaj,J (B1164 (3g` s
(3ChdgG (B:s
(3CeG HYO, ajbhd GdYHO GdabjQ eMeO Hf eMeO Hf eMehO GdCRgQi GdMfaiGf Yde GdaQGjV bO GTJgQJ aVjdJg s
(3BNQgG (B:s
(3hGKfGf dHfJi GdNGdg hLejY Pdc SJI hKdGKhf hcPG ai GdSQGLjI hTQhMgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQ GdLhGgQ GdHgjI aj EjVGM Gdecfhf (B376/1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B299s
Keywords: (3Yde GdaQGFVs